Proceedings of the 2013 International Conference on Advanced ICT 2013
DOI: 10.2991/icaicte.2013.28
|View full text |Cite
|
Sign up to set email alerts
|

Construction of the Online Test System for Common Basic Course in Colleges

Abstract: The teaching of common basic course in colleges has several drawbacks, such as teachers' subject and examination-driven approach. If teaching process was shifted from curriculum-centered to studentcentered, there was a great improvement in teaching even in education. This paper suggests that it should construct an online test system for common basic course. It is possible to solve some of the problems in teaching of common basic course by applying this online test system. In this online evaluation system, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…However, the above system found that, among the questions and generating paper module is mainly in the form of an objective choice and judgment-based. It is less applicable to Photoshop such a strong operational courses, Photoshop courses on the network it is difficult to find the test library management Test Paper System [3].…”
Section: The Photoshop Test Library Construction and Papers Automatic...mentioning
confidence: 99%
“…However, the above system found that, among the questions and generating paper module is mainly in the form of an objective choice and judgment-based. It is less applicable to Photoshop such a strong operational courses, Photoshop courses on the network it is difficult to find the test library management Test Paper System [3].…”
Section: The Photoshop Test Library Construction and Papers Automatic...mentioning
confidence: 99%
“…Whenever they get a question wrong, students are encouraged to re-visit the course materials and correct the mistakes as many times as they need. As mentioned in Wang, et al [4] the online evaluation system serves as a double driving force that enable students to go back to study. Students have total control of their grades in both categories and use these tests as ways to gain knowledge and critical thinking skills.…”
Section: Online Tests Motivate and Assess Students Learningmentioning
confidence: 99%